SISTEM INFORMASI MANAJEMEN DATA PRESTASI MAHASISWA MENGGUNAKAN PHP DAN MYSQL (STUDI KASUS UNIVERSITAS NAHDLATUL ULAMA KALIMANTAN SELATAN) - Sofyar, Sofyar; Rafii, Muhammad; Fajrian Noor, Muhammad; Najib, Najib (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
This study aims to develop an application that can store and manage student achievement data well to support increased efficiency in scholarship distribution. In addition, it also includes improving the selection process and student achievement assessment to be more accurate and transparent, as well as improving the quality of management of the achievement scholarship program at the Nahdlatul Ulama University of South Kalimantan (Unukase). This study used the prototype method. The method used in this study is the prototype method of software development models consisting of the stages of needs analysis, design, coding, and testing. This method allows researchers to get direct feedback from users during the system development process. The result of this study is a web-based application that helps manage student achievement data at Unukase.